Patient motives behind low-acuity visits to the emergency department in Germany: a qualitative study comparing urban and rural sites. Issue 11 (16th November 2016) - Schmiedhofer, Martina; Möckel, Martin; Slagman, Anna; Frick, Johann; Ruhla, Stephan; Searle, Julia
Abstract : Objectives: The increasing number of low-acuity visits to emergency departments (ED) is an important issue in Germany, despite the fact that all costs of inpatient and outpatient treatment are covered by mandatory health insurance. We aimed to explore the motives of patients categorised with low-acuity conditions for visiting an ED. Methods: We conducted a qualitative study in two urban and one rural ED. We recruited a purposive sample of adults, who were assigned to the lowest two categories in the Manchester triage system. One-to-one interviews took place in the ED during patients' waiting time for treatment. Interview transcripts were analysed using the qualitative data management software MAXQDA. A qualitative content analysis approach was taken to identify motives and to compare the rural with the urban sites. Results: A total of 86 patients were asked to participate; of these, n=15 declined participation and n=7 were excluded because they were admitted as inpatients, leaving a final sample of 40 female and 24 male patients. We identified three pathways leading to an ED visit: (1) without primary care contact, (2) after unsuccessful attempts to see a resident specialist or general practitioner (GP) and (3) recommendation to visit the ED by an outpatient provider. The two essential motives were (1) convenience and (2) health anxiety, triggered by time constraints and focused usage of multidisciplinary medical care in a highly equipped setting. All participants from the rural region were connected to a GP, whom they saw more or less regularly, while more interviewees from the urban site did not have a permanent GP. Still, motives to visit the ED were in general the same. Conclusions: We conclude that the ED plays a pivotal role in ambulatory acute care which needs to be recognised for adequate resource allocation. Trial registration number: DRK S00006053